The Deformation Behaviors and Mechanism of the High-Temperature Mechanical Properties of a Ni48W35Co17 Alloy - Guoliang Xie (MDPI AG, 2021)
Investigations of the plastic deformation mechanisms of Ni-W-based heavy alloys varying with increasing temperatures are very important for the development of hot forming processes and applications at elevated temperatures. In this study, the continuous variation of strength and plasticity of a novel Ni-W-based heavy alloy with increasing temperatures was investigated. The tensile strength of a Ni48W35Co17 sample at 600 °C was 471 MPa, which was 47% lower than that at 100 °C. A variation in an abnormal decrease in elongations at temperatures from 400 °C to 800 °C was found in this alloy. The elongation rate of the sample tensile at 600 °C was 19%, which was 73% lower than that at 100 °C. A microstructural analysis revealed that the number of twins in the sample tensile at a temperature higher than 600 °C increased considerably compared with the sample tensile at lower temperatures, indicating that the dislocation slips were suppressed during the high-temperature stretching process. The precipitates of the NiW phase were found in the 600 °C tensile sample, which was not clearly observed in the 400 °C tensile sample, suggesting that dislocation slips were affected by the formation of these precipitates. Moreover, the orientation relationship between the matrix and NiW phase was (200)Ni//(240)NiW and [001]Ni//[001]NiW. The tiny precipitated phase was the main reason for the plasticity decrease of the alloy with the temperature increase.